Indene thiophene dimer-based solar cell donor material and application thereof
By introducing indenothiophene-like dimers as donor materials in organic solar cells and combining them with the PM6:Y6 system, the problem of insufficient energy conversion efficiency and stability in the prior art is solved, and the energy conversion efficiency and material improvement are achieved The stability improvement provides a green and environmentally friendly solution.
Patent Information
- Application Number
- CN202411342700.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Existing organic solar cell devices have challenges in improving energy conversion efficiency and stability, especially because the absorption spectrum of organic semiconductor materials is narrow, making it difficult to effectively utilize solar energy, and donor materials are less used as the third component.
Design a tri-component device based on indenothiophene-based dimer as a donor material. By combining with the PM6:Y6 system, a tri-component device with PM6:Y6 is prepared, and the device structure is optimized to be ITO /PEDOT:PSS/PM6: Indenothiophene dimer donor material: Y6/PDINO/Ag, achieving an improvement in energy conversion efficiency.
It improves the energy conversion efficiency and stability of photovoltaic devices, provides a simple, green and environmentally friendly synthesis method, enhances the solubility and photovoltaic characteristics of the material, and improves the performance compared with haploids.
Smart Images

Figure CN119219670A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of organic solar cell donor materials and organic solar cell devices: 1. It relates to the preparation of a solar cell donor material based on indenothiophene dimer; 2. The material is used as the third component of an organic solar cell and doped in a PM6:Y6 system to prepare a bulk heterojunction organic photovoltaic cell device, and an energy conversion efficiency (PCE) of 17.06% is obtained, as well as a method for effectively improving device stability and PCE. Background Art
[0002] Organic solar cells are considered to be a new energy technology with great application prospects due to their outstanding advantages such as light weight, flexibility and the ability to prepare large-area devices. At present, the highest efficiency of single-active-layer binary organic solar cell devices has reached 19.70%. However, due to the narrow absorption spectrum of organic semiconductor materials, it is difficult to effectively utilize solar energy. In ternary organic solar cells (TOSCs), three different components are mixed together to form a photoactive layer, providing opportunities to improve power conversion efficiency, for example, by broadening the absorption range, improving the hybrid morphology or regulating exciton splitting and charge extraction. Due to these possibilities, ternary systems are one of the best performing OSCs and will play a vital role in the future of organic photovoltaics. At present, the third component of TOSCs has been reported to be mainly the acceptor material, and donor materials as the third component are rarely reported in the literature. Among them, oligomer donor materials have the advantages of both small molecules and polymers. Due to their excellent optoelectronic properties, charge transport properties, good stability and easy energy level regulation, they have always attracted wide attention in the development of organic solar cells. Summary of the invention
[0003] In view of the current research status of organic solar cell donor materials, the purpose of the present invention is to design a class of indenothiophene dimer-based solar cell donor materials to prepare bulk heterojunction organic solar cell devices, so as to achieve a new method for improving the power conversion efficiency (PCE).
[0004] The technical solution of the present invention is as follows:
[0005] A donor material for solar cells based on indenothiophene dimers, wherein the molecular structure of the dimer is:
[0006] Where R is C6-C 12 A type of straight chain alkyl.
[0007] A method for preparing a solar cell donor material based on an indenothiophene dimer, wherein the preparation of the molecular structure formula of the dimer comprises the steps of:
[0008] (1) The chemical structure is and 3-ethylrhodanine were added to a double-necked reaction bottle with a magnetic stirrer; the double-necked reaction bottle was evacuated and passed with N2, and piperidine was added to the reaction bottle to obtain a second reaction mixture;
[0009] (2) heating the second reaction mixture to a second predetermined temperature and stirring the mixture at the second predetermined temperature for a second predetermined time to obtain a second mixed product; purifying the second mixed product to obtain the dimer structural formula.
[0010] Indenothiophene dimer donor material is doped as the third component in the PM6:Y6 system to prepare a ternary device of PM6:indenothiophene dimer donor material:Y6; the mass ratio of PM6:Y6:indenothiophene dimer donor material is 1:1.2:0.05~0.2; the optimal mass ratio is 1:1.2:0.1.
[0011] The present invention also provides an application of an indenothiophene dimer solar cell donor material, wherein the device structure is: ITO / PEDOT:PSS (30nm) / PM6:dimer donor material:Y6 (100nm) / PDINO (5nm) / Ag (100nm). The active layer is based on PM6:indenothiophene dimer donor material:Y6.
[0012] Compared with the current technology, the beneficial effects of the present invention are as follows: the synthesis method of the dimer donor material provided by the present invention is simple, green and environmentally friendly, and has a high yield; the synthesized material has good stability and solubility, and after being prepared into a heterojunction device, the photovoltaic characteristics of the dimer are improved compared to those of the haploid. This shows that the dimer donor is an effective way to improve the photovoltaic performance and stability of photovoltaic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a structural diagram of an organic solar cell device according to the present invention;
[0014] Figure 2 The synthetic route of C6dIOEH-RDN32 and C12dIOEH-RDN32 in the present invention;
[0015] Figure 3 This is the H NMR spectrum of the intermediate 2 in Example 1 of the present invention;
[0016] Figure 4 This is the H NMR spectrum of Example 1C6dIOEH-RDN32 of the present invention;
[0017] Figure 5 This is the H NMR spectrum of Intermediate 2 of Example 2 of the present invention;
[0018] Figure 6This is the H NMR spectrum of Example 2C12dIOEH-RDN32 of the present invention;
[0019] Figure 7 The UV absorption diagram of the solution and solid film of Example 1C6dIOEH-RDN32 of the present invention;
[0020] Figure 8 The UV absorption diagram of the solution and solid film of Example 2C12dIOEH-RDN32 of the present invention;
[0021] Fig. 9 The UV absorption diagram of the solution and solid film of Comparative Example 1IOEH-RDN32 of the present invention;
[0022] Fig.10 1 is a cyclic voltammetry curve of C6dIOEH-RDN32 of Example 1 of the present invention;
[0023] Fig.11 is the current-voltage (JV) curve of the organic solar cell device of Example 1 of the present invention;
[0024] Fig.12 This is the current-voltage (JV) curve of the organic solar cell device of Comparative Example 1 of the present invention.
[0025] Fig.13 is the current-voltage (JV) curve of the organic solar cell device of Example 2 of the present invention; Specific implementation plan
[0026] The following specific examples are intended to further illustrate the present invention, but these specific embodiments do not limit the scope of protection of the present invention in any way.
[0027] Example 1
[0028] 1. Synthesis of C6dIOEH-RDN32:
[0029]
[0030] Compound 1 (180 mg, 0.18 mmol), 4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-dicarbaldehyde (DTC-CHO) (232 mg, 0.54 mmol) were dissolved in dry toluene (35 mL), CS2CO3 (234 mg, 0.72 mmol), pivalic acid (PiVOH) (18 mg, 0.18 mmol), Pd2(dba)3 (33 mg, 0.036 mg), tri(2-methoxyphenyl)phosphine (P(O-CH3OPh)3) (51 mg, 0.14 mmol) were added, and the mixture was reacted overnight at 110° C. under a nitrogen atmosphere. After the reaction was completed, the filtrate was filtered through a suction funnel, the filtrate was collected, the solvent was removed by a rotary evaporator, and the mixture was purified by silica gel column chromatography (the eluent was pure dichloromethane) to obtain an orange-yellow oily substance Compound 2 (125 mg, 44%). 1 H NMR (400MHz, Chloroform-d) δ9.90 (s, 2H), 9.83 (s, 2H), 7.63 (s, 2H), 7.59 (s, 4H), 7.52 (t, J=5.1Hz, 2H), 7.16 (s, 2H), 4.28 (t, J=6.1Hz, 4H), 2.13 (t, J=6.6Hz, 4H), 1.99 (dq, J=15.4, 4.8, 4.4Hz, 11H), 1.89 (td, J= 14.0, 13.3, 5.7Hz, 5H), 1.80 (d, J=6.6Hz, 4H), 1.36-1.22 (m, 6H), 1.19-1.04 (m, 27H), 0.99-0.94 (m, 15H) , 0.94-0.90 (m, 9H), 0.87-0.82 (m, 6H), 0.78 (t, J=6.9Hz, 11H), 0.73 (t, J=6.7Hz, 7H), 0.68-0.59 (m, 21H).
[0031] Compound 2 (190 mg, 0.11 mmol) and 3-ethylrhodanine (90 mg, 0.56 mmol) were dissolved in chloroform (20 mL), and then piperidine (1.5 mL) was added and reacted at 60 ° C under a nitrogen atmosphere for 12 h. After the reaction was completed, the reaction solution was slowly dripped into 100 mL of methanol for precipitation, and the mobile phase was filtered to obtain a crude product, which was purified by silica gel column chromatography (eluent: petroleum ether: dichloromethane = 1:1) to obtain a blue-purple solid C6dIOEH-RDN32 (140 mg, 70%). 1HNMR (400MHz, Chloroform-d) δ7.92 (s, 2H), 7.86 (s, 2H), 7.61 (d, J=2.5Hz, 2H), 7.52 (tt, J=5.1, 2.5Hz, 2H), 7.2 7 (s, 2H), 7.23 (d, J = 2.5Hz, 2H), 7.15 (s, 2H), 4.39-4.27 (m, 4H), 4.19 (t, J = 7.4Hz, 8H), 2.17 (t, J = 7.0Hz, 4H), 2.0 6-1.79 (m, 20H), 1.58 (s, 4H), 1.29 (q, J=7.4Hz, 12H), 1.20-1.05 (m, 24H), 1.04-0.89 (m, 31H), 0.84 (d, J=8.6Hz, 5H), 0.78 (t, J=6.9Hz, 14H), 0.72 (t, J=6.7Hz, 6H), 0.69-0.64 (m, 10H), 0.64-0.62 (m, 4H), 0.60 (d, J=7.5Hz, 6H).
[0032] 2. The device structure of the organic solar cell based on Example 1 is: ITO / PEDOT:PSS / active layer / PDINO / Ag. The mass ratio of the active layer PM6:Y6:C6dIOEH-RDN32 is 1:1.2:0.1. The production scheme is as follows:
[0033] Cleaning and pretreatment of ITO substrates
[0034] The ITO substrate was cleaned in an ultrasonic cleaner in the order of washing liquid (10 min), isopropanol (20 min), acetone (20 min), deionized water (10 min×4), and isopropanol (20 min), and dried in an oven overnight. Before use, the ITO surface was treated with UV ozone for 15 min and cooled to room temperature.
[0035] Spin coating of hole transport layer PEDOT:PSS
[0036] The PEDOT:PSS solution was spin coated at 2500 r / min for 30 s in a room temperature air environment, then baked at 100°C for 15 min, and then cooled at room temperature for 15 min to prepare a uniform and smooth film.
[0037] Mixing and spin coating of active layer materials
[0038] In a glove box with a nitrogen atmosphere, PM6:Y6:C6dIOEH-RDN32 with a mass ratio of 1:1.2:0.1 and a donor concentration of 10 mg / mL was dissolved in chloroform and spin-coated at 2500 r / min for 30 s, followed by annealing at different temperatures for 10 min and subsequent cooling at room temperature for 20 min to form a uniform and smooth film.
[0039] Spin coating of electron transport layer PDINO and evaporation of cathode Ag
[0040] In a glove box with a nitrogen atmosphere, PDINO with a concentration of 1 mg / mL was spin-coated at a speed of 3000 r / min for 30 s to prepare a uniform and smooth film. The spin-coated device was then placed in a vacuum evaporation chamber at 1×10 -5 A 100nm thick metal electrode Ag was evaporated on the active layer under Pa.
[0041] Device performance test
[0042] Under standard test conditions (AM1.5, 100mW / cm 2 ), and measure the device’s V oc =0.871V, J sc =25.43mA / cm 2 , FF=76.90%, PCE=17.05%.
[0043] Table 1. Performance parameters of PM6:Y6:C6dIOEH-RDN32 devices under different ratios
[0044]
[0045] Comparative Example 1
[0046] 1. Synthesis of haploid IOEH-RDN32
[0047]
[0048] Compound 1 (100 mg, 0.11 mmol) and 3-ethylrhodanine (52 mg, 0.32 mmol) were dissolved in chloroform (20 mL), and then piperidine (1.5 mL) was added, and the mixture was reacted at 60 ° C under a nitrogen atmosphere for 12 h. After the reaction, the reaction solution was slowly dripped into 100 mL of methanol for precipitation, and the mobile phase was filtered to obtain a crude product, which was purified by silica gel column chromatography (eluent: petroleum ether: dichloromethane = 1:1) to obtain a blue-purple solid (92 mg, 70%). 1HNMR (400MHz, CDCl3) δ7.84 (s, 1H), 7.81 (d, J = 2.6Hz, 1H), 7.46 (s, 1H), 7.43 (d, J = 4.3Hz, 1H), 7.18 (d, J = 4.3Hz, 1H), 7.1 5 (d, J=2.6Hz, 1H), 7.03 (s, 1H), 4.12 (q, J=7.1Hz, 4H), 4.02 (d, J=5.6Hz, 2H), 0.69 (t, J=6.9Hz, 6H), 2.00-0.40 (m, 75H).
[0049] 2. The device structure of the solar cell based on Comparative Example 1 is: ITO / PEDOT:PSS / IOEH-RDN32:Y6 / PDINO / Ag. The mass ratio of the active layer PM6:Y6:IOEH-RDN32 is 1:1.2:0.1. Its production scheme is as follows:
[0050] Cleaning and pretreatment of ITO substrates
[0051] The ITO substrate was cleaned in an ultrasonic cleaner in the order of washing liquid (10 min), isopropanol (20 min), acetone (20 min), deionized water (10 min×4), and isopropanol (20 min), and dried in an oven overnight. Before use, the ITO surface was treated with UV ozone for 15 min and cooled to room temperature.
[0052] Spin coating of hole transport layer PEDOT:PSS
[0053] The PEDOT:PSS solution was spin coated at 2500 r / min for 30 s in a room temperature air environment, then baked at 100°C for 15 min, and then cooled at room temperature for 15 min to prepare a uniform and smooth film.
[0054] Mixing and spin coating of active layer materials
[0055] In a glove box with a nitrogen atmosphere, PM6:Y6:IOEH-RDN32 was dissolved in chloroform with a mass ratio of 1:1.2:0.1 and a donor concentration of 10 mg / mL, and spin-coated at 2500 r / min for 30 s, followed by annealing at 100 °C for 10 min and subsequent cooling at room temperature for 20 min to form a uniform and smooth film.
[0056] Spin coating of electron transport layer PDINO and evaporation of cathode Ag
[0057] In a glove box with a nitrogen atmosphere, PDINO with a concentration of 1 mg / mL was spin-coated at a speed of 3000 r / min for 30 s to prepare a uniform and smooth film. The spin-coated device was then placed in a vacuum evaporation chamber at 1×10 -5 A 100nm thick metal electrode Ag was evaporated on the active layer under Pa.
[0058] Device performance test
[0059] Under standard test conditions (AM1.5, 100mW / cm 2 ), and measure the device’s V oc =0.868V, J sc =25.59mA / cm 2 , FF=75.99%, PCE=16.89%.
[0060] The absorption spectra of C6dIOEH-RDN32 and IOEH-RDN32 in chloroform solution and film state were tested by UV-visible spectrophotometer. In dilute chloroform solution, C6dIOEH-RDN32 showed strong absorption in the 440-650nm region, with maximum absorption at 552nm; IOEH-RDN32 showed strong absorption in the 450-642nm region, with maximum absorption at 570nm. The dimer has a wider absorption spectrum range than the haploid; in the pure film state, the absorption curves of C6dIOEH-RDN32 and IOEH-RDN32 have obvious red shifts compared with their respective solutions. Compared with the haploid, the absorption of the dimer has a blue shift, which is because the flexible linker connects the two small molecules together, reducing the diffusion rate of the molecules.
[0061] The C6dIOEH-RDN32 prepared by the present invention was subjected to an electrochemical test. The C6dIOEH-RDN32 was dissolved in chloroform to form a solution with a concentration of 1 mg / mL, and was dripped onto the working electrode (the dripping diameter was 2 mm). A 0.1M Bu4NPF6 acetonitrile solution was used as the electrolyte, a platinum wire was used as the counter electrode, Ag / Ag+ was used as the reference electrode, and ferrocene was used as the standard. The redox potential was measured using electrochemical cyclic voltammetry, and the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) were calculated.
[0062]
[0063] E g =1240 / λ=1240 / 800=1.55
[0064] LUMO=HOMO+E g =-5.41+1.55=-3.86eV
[0065] Example 2
[0066] 1. Synthesis of C12dIOEH-RDN32:
[0067]
[0068] Compound 1 (362 mg, 0.41 mmol) and DTC-CHO (535 mg, 1.24 mmol) were dissolved in dry toluene (80 mL), and CS2CO3 (539 mg, 1.66 mmol), PiVOH (42 mg, 0.41 mmol), Pd2(dba)3 (76 mg, 0.083 mg), and P(O-CH3OPh)3 (117 mg, 0.33 mmol) were added, and the mixture was reacted overnight at 110°C under a nitrogen atmosphere. After the reaction was completed, the filtrate was filtered through a suction funnel, the filtrate was collected, the solvent was removed by a rotary evaporator, and the mixture was purified by silica gel column chromatography (the eluent was pure dichloromethane) to obtain an orange-yellow oily substance Compound 2 (125 mg, 44%). 1 H NMR (400MHz, Chloroform-d) δ9.90 (s, 2H), 9.83 (s, 2H), 7.63 (s, 2H), 7.57 (d, J=5.8Hz , 4H), 7.52 (d, J=4.4Hz, 2H), 7.15 (s, 2H), 4.22 (t, J=6.6Hz, 4H), 2.08-1.93 (m, 16H), 1. 89 (t, J=11.1Hz, 5H), 1.61 (p, J=7.3Hz, 4H), 1.49-1.32 (m, 13H), 1.19-1.07 (m, 25H), 1 .02-0.89 (m, 30H), 0.79 (td, J=17.1, 14.9, 6.0Hz, 27H), 0.64 (dt, J=14.7, 6.9Hz, 20H).
[0069] Compound 2 (202 mg, 0.11 mmol) and 3-ethylrhodanine (91 mg, 0.56 mmol) were dissolved in chloroform (20 mL), and then piperidine (1.5 mL) was added and reacted at 60 ° C under nitrogen atmosphere for 12 h. After the reaction was completed, the reaction solution was slowly dripped into 100 mL of methanol for precipitation, and the mobile phase was filtered to obtain a crude product, which was purified by silica gel column chromatography (eluent: petroleum ether: dichloromethane = 1:1) to obtain a blue-purple solid C12dIOEH-RDN32 (186 mg, 70%). 1H NMR (400MHz, Chloroform-d) δ7.94 (s, 2H), 7.92 (d, J = 2.4Hz, 2H), 7.58 (s, 2H), 7.53 (d, J = 4.4Hz, 2 H), 7.28 (d, J=3.0Hz, 3H), 7.25 (s, 1H), 7.13 (s, 2H), 4.33-4.11 (m, 12H), 2.00 (ddt, J=31.7, 26.3, 7.2Hz, 20H), 1.64 (dt, J=12.0, 5.6Hz, 5H), 1.55-1.41 (m, 12H), 1.31 (td, J=7.2, 3.7Hz, 13H), 1.16 (dt, J=18.0, 5.8Hz, 23H), 1.05-0.91 (m, 31H), 0.88-0.73 (m, 27H), 0.66 (dt, J=19.6, 6.6Hz, 21H).
[0070] 2. The device structure of the organic solar cell based on Example 2 is: ITO / PEDOT:PSS / active layer / PDINO / Ag. The mass ratio of the active layer PM6:Y6:C12dIOEH-RDN32 is 1:1.2:0.1. The production scheme is as follows:
[0071] Cleaning and pretreatment of ITO substrates
[0072] The ITO substrate was cleaned in an ultrasonic cleaner in the order of washing liquid (10 min), isopropanol (20 min), acetone (20 min), deionized water (10 min×4), and isopropanol (20 min), and dried in an oven overnight. Before use, the ITO surface was treated with UV ozone for 15 min and cooled to room temperature.
[0073] Spin coating of hole transport layer PEDOT:PSS
[0074] The PEDOT:PSS solution was spin coated at 2500 r / min for 30 s in a room temperature air environment, then baked at 100°C for 15 min, and then cooled at room temperature for 15 min to prepare a uniform and smooth film.
[0075] Mixing and spin coating of active layer materials
[0076] In a glove box with a nitrogen atmosphere, PM6:Y6:C12dIOEH-RDN32 with a mass ratio of 1:1.2:0.1 and a donor concentration of 10 mg / mL was dissolved in chloroform and spin-coated at 2500 r / min for 30 s, followed by annealing at different temperatures for 10 min and subsequent cooling at room temperature for 20 min to form a uniform and smooth film.
[0077] Spin coating of electron transport layer PDINO and evaporation of cathode Ag
[0078] In a glove box with a nitrogen atmosphere, PDINO with a concentration of 1 mg / mL was spin-coated at a speed of 3000 r / min for 30 s to prepare a uniform and smooth film. The spin-coated device was then placed in a vacuum evaporation chamber at 1×10 -5 A 100nm thick metal electrode Ag was evaporated on the active layer under Pa.
[0079] Device performance test
[0080] Under standard test conditions (AM1.5, 100mW / cm 2 ), and measure the device’s V oc =0.871V, J sc =25.91mA / cm 2 , FF=75.57%, PCE=17.06%.
[0081] The absorption spectra of C12dIOEH-RDN32 in chloroform solution and in thin film state were tested using a UV-visible spectrophotometer. In dilute chloroform solution, C12dIOEH-RDN32 showed strong absorption in the 437-658nm region and had maximum absorption at 550nm. In the pure film state, compared with the solution, the absorption curves of C12dIOEH-RDN32 and IOEH-RDN32 had an obvious red shift.
[0082] Table 2. Performance parameters of the PM6:Y6:C12dIOEH-RDN32 device under different ratio conditions
[0083]
[0084] Table 3. Device performance parameters based on PM6:Y6 at the optimal ratio under different third component conditions
[0085]
[0086] Although the present invention has been described in conjunction with the preferred embodiments, the present invention is not limited to the above embodiments, and it should be understood that the appended claims summarize the scope of the present invention. Under the guidance of the inventive concept, those skilled in the art should be aware that certain changes made to the various embodiments of the present invention will be covered by the spirit and scope of the claims of the present invention.
Claims
1. A donor material for solar cells based on indenothiophene dimers, characterized in that: The chemical structure formula of the donor material is: Where R is C6-C 12 A type of straight chain alkyl.
2. The indenothiophene dimer-based solar cell donor material according to claim 1, characterized in that: The dimer donor is one of C6dIOEH-RDN32 and C12dIOEH-RDN32; Among them, the chemical structure formula of C6dIOEH-RDN32 is: The chemical structure of C12dIOEH-RDN32 is:
3. The use of the indenothiophene dimer-based solar cell donor material according to claim 1 or 2, characterized in that: The indenothiophene dimer is used as a donor material in a solar cell device.
4. The use of the indenothiophene dimer-based solar cell donor material according to claim 3, characterized in that: The indenothiophene dimer donor material is doped as the third component in the PM6:Y6 system to prepare a ternary device of PM6:indenothiophene dimer donor material:Y6.
5. The use of the indenothiophene dimer-based solar cell donor material according to claim 4, characterized in that: The mass ratio of PM6: indenothiophene dimer donor material: Y6 is 1:0.05~0.2:1.
2.
6. The use of the indenothiophene dimer-based solar cell donor material according to claim 5, characterized in that: The mass ratio of PM6: indenothiophene dimer donor material: Y6 is 1:0.1:1.
2.
7. The use of the indenothiophene dimer-based solar cell donor material according to claim 4, characterized in that: The device structure is: ITO / PEDOT:PSS / PM6:dimer donor material: Y6 / PDINO / Ag.
Citation Information
Patent Citations
Conjugated organic molecule, photoactive layer material, ternary organic solar cell and preparation method of ternary organic solar cell
CN115785126A
KR20190052333A
